Making sense of SNPs: Women's understanding and experiences of receiving a personalized profile of their breast cancer risks - Young, M; Forrest, L; Rasmussen, V; James, P; Mitchell, G; Sawyer, S; Reeve, K; Hallowell, N (Springer US, 2017)
Genome wide association studies have identified a number of common genetic variants - single nucleotide polymorphisms (SNPs) – that combine to increase breast cancer risk. SNP profiling may enhance the accuracy of risk assessment and provides a personalized risk estimate. SNP testing for breast cancer risks may supplement other genetic tests in the future, however, before it can be implemented in the clinic we need to know how it will be perceived and received. Semi-structured qualitative interviews were conducted with 39 women who had previously had a breast cancer diagnosis and undergone BRCA1/2 testing, participated in the Variants in Practice (ViP) study and received personalized risk (SNP) profiles. Interviews explored their understanding and experiences of receiving this SNP information. Women reported feeling positive about receiving their personalized risk profile, because it: provided an explanation for their previous diagnosis of cancer, vindicated previous risk management decisions and clarified their own and other family members’ risks. A small group was initially shocked to learn of the increased risk of a second primary breast cancer. This study suggests that the provision of personalized risk information about breast cancer generated by SNP profiling is understood and well received. However, a model of genetic counseling that incorporates monogenic and polygenic genetic information will need to be developed prior to clinical implementation.